Joint effects of intensity and duration of cigarette smoking on the risk of head and neck cancer: A bivariate spline model approach. (July 2019) - Di Credico, Gioia; Edefonti, Valeria; Polesel, Jerry; Pauli, Francesco; Torelli, Nicola; Serraino, Diego; Negri, Eva; Luce, Daniele; Stucker, Isabelle; Matsuo, Keitaro; Brennan, Paul; Vilensky, Marta; et al.
Highlights: Oral cancer risk >5 emerged for smokers of >20 cigarettes/day for >30 years. Laryngeal cancer risk >20 emerged for smokers of >20 cigarettes/day for >30 years. Former smokers since ≥10 years ( vs. current) halved their head and neck cancer risk. Spline models allow a more accurate estimation of joint exposures on cancer risk. Abstract: Objectives: This study aimed at re-evaluating the strength and shape of the dose-response relationship between the combined (or joint) effect of intensity and duration of cigarette smoking and the risk of head and neck cancer (HNC). We explored this issue considering bivariate spline models, where smoking intensity and duration were treated as interacting continuous exposures. Materials and Methods: We pooled individual-level data from 33 case-control studies (18, 260 HNC cases and 29, 844 controls) participating in the International Head and Neck Cancer Epidemiology (INHANCE) consortium. In bivariate regression spline models, exposures to cigarette smoking intensity and duration (compared with never smokers) were modeled as a linear piecewise function within a logistic regression also including potential confounders. We jointly estimated the optimal knot locations and regression parameters within the Bayesian framework. Results: For oral-cavity/pharyngeal (OCP) cancers, an odds ratio (OR) >5 was reached after 30 years in current smokers of ∼20 or more cigarettes/day. Patterns of OCP cancer risk in current smokers differed across strata of alcohol intensity. For laryngeal cancer, ORs >20 were found for current smokers of ≥20 cigarettes/day for ≥30  years. In former smokers who quit ≥10  years ago, the ORs were approximately halved for OCP cancers, and ∼1/3 for laryngeal cancer, as compared to the same levels of intensity and duration in current smokers. Conclusion: Referring to bivariate spline models, this study better quantified the joint effect of intensity and duration of cigarette smoking on HNC risk, further stressing the need of smoking cessation policies.